AKTIVITAS l'ENGASUHAN SEBAGAIPREDIKTOR TINGKAHLAKU BERMASALAH - Eka Izzaty, Rita (Jurnal Cakrawala Pendidikan, 2016)
Behavior problem is often observed among clilldren. Ecological Theory depicts interaction of environmental factors which ihflllence children's development. Earenting practices is one of factors that has been identified as predictors of the prpblem.emotional and social support, monitoring, and discipline are central dimensions of parental practices that are linked with children's adjustment, development, and welbbeing. A meta -analysis of 51 studies examining the relationship between parenting practices and externalizing behavior problems, 'inyolving 13 researchers and 49564 subjects, is reported. This analysis extends previous works in the sense that it integrates diverse findings by correcting errors Qf sampling and measurements. The results show that several dimensions in parenting practices, namely emosional and social support, monitoring, and discipline are significant predictQrs of externalizing behavior problems.